931. RHODODENDRON SUOILENHENSE. (8th February 2020) - Rushforth, Keith; Huong, Nguyen Thi Thanh; Chamberlain, David
Summary: A new species of Rhododendron, R. suoilenhense D.F. Chamberlain, Nguyen Thi Thanh Huong & Rushforth, is described from northern Vietnam and illustrated. Its discovery and distribution are noted. Suggestions for its cultivation are given.